Research performance evaluation using Data Envelopment Analysis (DEA) / Norshahida Shaadan (Fakulti Teknologi Maklumat dan Sains Kuantitatif, 2005)
This paper seeks to evaluate the research performance of 29 research units in terms of productivity and efficiency via DEA. This objective is achieved by establishing a set of performance indicators particularly in the aspect of relative efficiency that covers both input and output factors. In this context, the relative efficiency of 29 participating units including (faculties and branch campuses) was measured using a non-parametric method namely, the Data Envelopment Analysis (DEA). DEA is able to handle the problems of multiple output and multiple input criteria and successfully assessed the overall performance of each research unit. In this particular problem, the overall performance can be interpreted as the achievement of all output criteria. The results revealed that 19 out of 29 units were efficient and known as the "best practice" units. It was also identified that the time spent to complete a project and the number of completed projects have being the most frequent contributing input and output criterion to the efficiency rating in the context of research performance evaluation.